Pengembangan Model Manajemen Stratejik (Wheelen and Hunger) - Machmud, Pajar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The company where I work is a company that falls into the manufacturing industry category, operating since 2011 in the Bukit Indah City Industrial Area, Purwakarta. The company I work for is in a good competitive position when compared to competing companies. Unipres is in the top ten largest press and stamping companies. One of the competitors for the press and stamping industry in Indonesia is Toyota Boshoku Indonesia. Competitive position of PT. Unipres Indonesia is in the good category because it has succeeded in controlling the stamping market for several car models such as Nissan, Honda, Mitsubishi, Isuzu, Suzuki and Hino. Environmental scanning is monitoring, evaluating, and searching for information from the external and internal environment for important people in the company. The aim is to identify strategic factors, external and internal elements that will determine the company's future. Strategy formulation, especially strategic planning or long-term planning, is usually related to the vision, mission and policies of an agency. Usually strategy development begins with analyzing the situation to find a match between external opportunities and internal strengths with external threats and internal weaknesses.